Sputum is a surrogate for bronchoalveolar lavage for monitoring Mycobacterium tuberculosis transcriptional profiles in TB patients. (September 2016) - Garcia, Benjamin J.; Loxton, Andre G.; Dolganov, Gregory M.; Van, Tran T.; Davis, J. Lucian; de Jong, Bouke C.; Voskuil, Martin I.; Leach, Sonia M.; Schoolnik, Gary K.; Walzl, Gerhard; Strong, Michael; Walter, Nicholas D.
Summary: Pathogen-targeted transcriptional profiling in human sputum may elucidate the physiologic state of Mycobacterium tuberculosis ( M. tuberculosis ) during infection and treatment. However, whether M. tuberculosis transcription in sputum recapitulates transcription in the lung is uncertain. We therefore compared M. tuberculosis transcription in human sputum and bronchoalveolar lavage (BAL) samples from 11 HIV-negative South African patients with pulmonary tuberculosis. We additionally compared these clinical samples with in vitro log phase aerobic growth and hypoxic non-replicating persistence (NRP-2). Of 2179 M. tuberculosis transcripts assayed in sputum and BAL via multiplex RT-PCR, 194 (8.9%) had a p-value <0.05, but none were significant after correction for multiple testing. Categorical enrichment analysis indicated that expression of the hypoxia-responsive DosR regulon was higher in BAL than in sputum. M. tuberculosis transcription in BAL and sputum was distinct from both aerobic growth and NRP-2, with a range of 396–1020 transcripts significantly differentially expressed after multiple testing correction. Collectively, our results indicate that M. tuberculosis transcription in sputum approximates M. tuberculosis transcription in the lung. Minor differences between M. tuberculosis transcription in BAL and sputum suggested lower oxygen concentrations or higher nitric oxide concentrations in BAL. M. tuberculosis- targeted transcriptional profiling of sputa may be a powerful tool for understanding M. tuberculosis pathogenesis and monitoring treatment responses in vivo .